The State's Right to Control (Droit De Regalie): The Regulatory Regime of Airspace and Outer Space in National Agrarian Law - Hendi Setiawan; Gita Ranjani; Graita Alfalaq Badnah (Universitas Sriwijaya, 2026)
This study examines the legal issue (juridical polemic) regarding the status of